Germany and the euroland crisis: The making of a vulnerable haven - Jörg Bibow (Levy Economics Institute of Bard College, 2013)
This paper investigates Germany's vulnerability to the ongoing Euroland crisis. In 2010-11, Germany experienced a strong rebound from the global financial crisis of 2008-09. The Euroland crisis then meant record low interest rates and a depressed euro that boosted German extra-area exports. But the crisis that started in Euroland's so-called periphery has meanwhile reached the core. With pro-euro sentiments dwindling fast across the European Union (EU), the future of the euro remains uncertain no matter what European Central Bank President Mario Draghi may promise. Germany's safe haven status may turn out to be a double-edged sword. In case of a euro breakup, swift appreciation of the new deutschmark would abruptly worsen German competitiveness and the German economy would crater as a result. Additional wealth losses on Germany's international investment position would also loom. Appreciating Germany's own vulnerability to the euro crisis should help the German authorities to understand that their policy prescriptions are anything but in Germany's own best interest, which is also good for the authorities in euro partner countries to recognize. Germany is bound to catch up with the reality that it is very vulnerable to the enormous wreckage and unnecessary hardship German-style policies are causing across Europe. The EU, most likely under French leadership, will have to convince Germany to embark on a fundamental policy course change, or else call an ugly end to the euro disaster.
Keywords: E42; E52; E58; E65; F36; G01; 330; Euro; Monetary Union; Banking Crisis; Balance-of-Payments Crisis; Competitiveness Imbalances; Fiscal Transfers; Bailouts; Austerity; Euro Breakup